Immunoelectrophoretic analysis of paramphistomid antigens - Maji, B P; Dwivedi, P; Rao, J R (The Indian Journal of Animal Sciences, 2012)
Immunoelectrophoretic analysis of paramphistomid antigens from 2 predominant rumainal flukes Paramphistomum epichtum and Gastrothylax crumenifer and a hepatic paramphistome Gigantocotyle explanatum showed a close antigenic relationship between the flukes. Three common antigenic components each in whole worm extract antigen (WWE-Ag) and detergent solubilized antigen (DS-Ag) and 2 in excretory-secretory antigen (ES-Ag) were observed. A notable cross-antigenicity was further demonstrated between P. epiclitum and G. explanatum in WWE-Ag (2 out of 5). DS-Ag (4 out of 5) and ES-Ag (2 out of 4) in reciprocal cross - testing. Cross - reacting ES-antigen of G. explanatum with P epiclitum (2) and G crumenfer (1) were also in evidence.